2015
DOI: 10.3347/kjp.2015.53.5.597
|View full text |Cite
|
Sign up to set email alerts
|

Activation of MAPK Is Required for ROS Generation and Exocytosis in HMC-1 Cells Induced by <i>Trichomonas vaginalis</i>-Derived Secretory Products

Abstract: Trichomonas vaginalis is a flagellated protozoan parasite that causes vaginitis and cervicitis in women and asymptomatic urethritis and prostatitis in men. Mast cells have been reported to be predominant in vaginal smears and vaginal walls of patients infected with T. vaginalis. Mitogen-activated protein kinase (MAPK), activated by various stimuli, have been shown to regulate the transcriptional activity of various cytokine genes in mast cells. In this study, we investigated whether MAPK is involved in ROS gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Surprising, this study showed that NF- κ B nuclear translocation occurred at 1 h transiently in T. vaginalis -treated SiHa cells and then declined at 4 h posttreatment. Narantsogt et al [ 21 ] also demonstrated that NF- κ B translocation occurs within 1 h of T. vaginalis adhesion and translocation drops dramatically by 8 h postadhesion. Considering the host-parasite relationship, early activation of NF- κ B nuclear translocation may be related to the protection from apoptotic cell death by T. vaginalis ; subsequently, T. vaginalis inhibits NF- κ B activity and leads to apoptosis in SiHa cells as a results of failure of NF- κ B p50 : p65 heterodimers to translocate to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprising, this study showed that NF- κ B nuclear translocation occurred at 1 h transiently in T. vaginalis -treated SiHa cells and then declined at 4 h posttreatment. Narantsogt et al [ 21 ] also demonstrated that NF- κ B translocation occurs within 1 h of T. vaginalis adhesion and translocation drops dramatically by 8 h postadhesion. Considering the host-parasite relationship, early activation of NF- κ B nuclear translocation may be related to the protection from apoptotic cell death by T. vaginalis ; subsequently, T. vaginalis inhibits NF- κ B activity and leads to apoptosis in SiHa cells as a results of failure of NF- κ B p50 : p65 heterodimers to translocate to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that dioscin (a natural product) and casticin (one of the main components of Fructus viticis ) induce apoptosis of HeLa and SiHa cells by promoting ROS-mediated DNA damage and the mitochondrial signaling pathway [ 19 , 20 ]. Activation of MAPK is required for ROS generation and exocytosis in HMC-1 cells by T. vaginalis -derived secretory products [ 21 ]. T. vaginalis induces IL-1 β production in human prostate epithelium through activation of ROS [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It also serves as the dominant system in regulating the production of MMPs, devoting to the degeneration of chondrocytes. Now it is approved that the Jun N‐terminal kinase (JNK), extracellular signal‐regulated kinase (ERK), and p38 in MAPK families are involved in the OA process . However, more research is required, as the mechanisms of MAPKs in OA are not exactly known.…”
Section: Introductionmentioning
confidence: 99%
“…TvSP induced upregulation of CD63 expression and reactive oxygen species (ROS) generation in HMC-1 cells via activation of mitogen-activated protein kinases (MAPKs) (35). T. vaginalis-derived LTB 4 can induce HMC-1 cells to release IL-8 via LTB 4 receptor (BLT)-dependent activation of NF-B and CREB (21).…”
mentioning
confidence: 99%
“…In previous studies, we found that TvSP or T. vaginalis-derived LTB 4 can induce exocytosis and interleukin-8 (IL-8) production in human granulocytes (34)(35)(36)(37). TvSP induced upregulation of CD63 expression and reactive oxygen species (ROS) generation in HMC-1 cells via activation of mitogen-activated protein kinases (MAPKs) (35).…”
mentioning
confidence: 99%